Concentrations of trace metals, phthalates, bisphenol A and flame-retardants in toys and other children's products in Israel. (February 2018) - Negev, Maya; Berman, Tamar; Reicher, Shay; Sadeh, Maya; Ardi, Ruti; Shammai, Yaniv
Abstract: Trace metals and synthetic chemicals including phthalates, bisphenol A and flame retardants, are widely used in toys and childcare products, and may pose acute or chronic adverse health effects in children. In Israel, certain chemicals are regulated in childcare products, but there are still regulatory gaps. We tested regulated and unregulated contaminants in 174 item parts from 70 childcare items with potentially high oral or dermal exposure, including 22 children's jewelry items, 14 toys, 7 diaper-changing mats, 6 baby mattresses, 7 baby textiles and 14 feeding and bathing items. In children's jewelry, an unregulated product in Israel, 23% of samples exceeded the US standard for lead. In toys, a regulated product, we did not detect trace metals above the Israeli standard. In textiles, baby mattresses and diaper-changing mats, phthalates exceeded the European Union standard in 14–45% of tests with a mean of 6.74% by mass for diisononyl phthalate, and 1.32% by mass for di(2-ethylhexyl) phthalate. BPA migration exceeded the EU standard in 14–45% of tests with a mean of 1.03 ppm. The flame retardants polybrominated biphenyls, pentabromodiphenyl, octabromodiphenyl ether, tris(2, 3-dibromopropyl) phosphate and tris-(aziridinyl)-phosphine oxide were not detected. For products regulated in Israel, our findings suggest general compliance with mandatory standards. However, a lack of comprehensive chemical regulation means that there are regulatory gaps, and products not regulated in Israel may contain high levels of chemical contamination, exceeding US or EU regulations. The results of this study have prompted the development of an Israeli safety standard for children's jewelry. Graphical abstract: Highlights: In children's jewelry, 23% exceeded the US lead standard. In selected childcare products, up to 45% exceeded the EU phthalates and BPA standards. Regulated products generally comply with standards, unregulated products are contaminated.